Hubungan Antara Kebersihan Diri dan Lama Tinggal dengan Kejadian Penyakit Skabies di Pon-Pes Al-Hamdulillah Rembang - Azizah, Novi Nur, Ambarwati, S.Pd, M.Si, Sri Darnoto, SKM., MPH (2013)
Boarding school represent santriwan place and santriwati to claim science. Skabies represent disease which identic with maisonette child. This matter causing because condition of less hygiene awake and ugly sanitation. Especial target of this research is to know relation between personal hygiene and long stay with infection of skabies disease. This research type is observasional with approach of cross sectional. Population in this research counted 380 santriwati and santriwan in boarding school Al-Hamdulillah Rembang. Sampel obtained by counted 60 one who is determined with random sampling sampel technique. Result of research show: There is relation between bath frequency (P=0,000), use soap (P=0,000), changing soap with friend (P=0,022), shampooing (P=0,000), changing clotes (p=0,015)changing clothes with friend (P=0,000), old remain (P=0,000) with infection skabies disease in boarding school Al-Hamdulillah Rembang. Suggested other researcher can check relevant other variable factors related to occurence of skabies besides hygiene variable and length of stay, for example pattern eat.